2006
DOI: 10.1080/01485010600664024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcium Channel Blockers on the Spermatogenesis and Gene Expression in Peripubertal Mouse Testis

Abstract: Treatment of Ca(2+) channel blockers (CCB) to relieve hypertension causes reversible male infertility, suggesting deregulation of Ca(2+) homeostasis in testis is closely related with male infertility. To investigate the possible toxicity of therapeutic application of CCB in childhood, the effect of nifedipine and ethosuximide, an L-type and T-type CCB, respectively, on the spermatogenesis and testicular gene expression was examined. Following the intraperitoneal injection of either drug for 7 days to 18 days o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The deleterious effects of Ca 2C channel blockers on male fertility emphasize even more the importance of tight Ca 2C regulation to spermatogenesis (Juneja et al 1990, Benoff et al 1994, Almeida et al 2000, Lee et al 2006, 2011. The common cellular localization pattern observed in rat and human testis, together with the wide cellular distribution of RGN indicate a relevant role in testicular physiology suggesting that RGN may play a role in spermatogenesis as a Ca 2C homeostasis regulator in both somatic and germ cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deleterious effects of Ca 2C channel blockers on male fertility emphasize even more the importance of tight Ca 2C regulation to spermatogenesis (Juneja et al 1990, Benoff et al 1994, Almeida et al 2000, Lee et al 2006, 2011. The common cellular localization pattern observed in rat and human testis, together with the wide cellular distribution of RGN indicate a relevant role in testicular physiology suggesting that RGN may play a role in spermatogenesis as a Ca 2C homeostasis regulator in both somatic and germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…The tight regulation of Ca 2C influx and outflux maintaining intracellular Ca 2C homeostasis also seems to be essential for Leydig cells (LC) steroidogenesis, for example by controlling the expression of STAR protein (Manna et al 1999, Pandey et al 2010. Moreover, it has been shown that administration of Ca 2C channel blockers has deleterious effects on mammalian spermatogenesis, being associated with reversible infertility (Juneja et al 1990, Benoff et al 1994, Almeida et al 2000, Lee et al 2006, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that sperm motility is dependent on an influx of free Ca ions. Thus, Ca channel blockers can lead to a reversible loss in sperm motility (30). In the present study, we found that the calcium and magnesium contents were low in the serum in subjects with azoospermia, but we could not find any differences in either the sperm or urine of the patients.…”
Section: Discussionmentioning
confidence: 47%
“…It is widely distributed in different tissues including liver, kidney, brain, testis, lungs, adrenal gland, stomach, ovary, uterus and epidermis (Feng et al, 2004). The RGN is a multifunctional protein with effects in calcium homeostasis, L-ascorbic acid biosynthesis, suppression of cell proliferation and apoptosis (Benoff et al, 1994;Franchi and Camatini, 1985;Grima et al, 1998;Hershlag et al, 1995;Juneja et al, 1990;Lee et al, 2006;Walker, 2009;Xu et al, 2007). Further, regucalcin is reported to have seven high affinity calcium binding sites (Yamaguchi and Sugii, 1981) and plays important role in calcium regulation in spermatogenesis and male fertility .…”
Section: Introductionmentioning
confidence: 99%